Transmission routes of antibiotic resistant bacteria: a systematic review - Godijk, Noortje G; Bootsma, Martin C J; Bonten, Marc J M (BioMed Central Ltd., 2022)
BACKGROUND: Quantification of acquisition routes of antibiotic resistant bacteria (ARB) is pivotal for understanding transmission dynamics and designing cost-effective interventions. Different methods have been used to quantify the importance of transmission routes, such as relative risks, odds ratios (OR), genomic comparisons and basic reproduction numbers. We systematically reviewed reported estimates on acquisition routes' contributions of ARB in humans, animals, water and the environment and assessed the methods used to quantify the importance of transmission routes. METHODS: PubMed and EMBASE were searched, resulting in 6054 articles published up until January 1st, 2019. Full text screening was performed on 525 articles and 277 are included. RESULTS: We extracted 718 estimates with S. aureus (n = 273), E. coli (n = 157) and Enterobacteriaceae (n = 99) being studied most frequently. Most estimates were derived from statistical methods (n = 560), mainly expressed as risks (n = 246) and ORs (n = 239), followed by genetic comparisons (n = 85), modelling (n = 62) and dosage of ARB ingested (n = 17). Transmission routes analysed most frequently were occupational exposure (n = 157), travelling (n = 110) and contacts with carriers (n = 83). Studies were mostly performed in the United States (n = 142), the Netherlands (n = 87) and Germany (n = 60). Comparison of methods was not possible as studies using different methods to estimate the same route were lacking. Due to study heterogeneity not all estimates by the same method could be pooled. CONCLUSION: Despite an abundance of published data the relative importance of transmission routes of ARB has not been accurately quantified. Links between exposure and acquisition are often present, but the frequency of exposure is missing, which disables estimation of transmission routes' importance. To create effective policies reducing ARB, estimates of transmission should be weighed by the frequency of exposure occurrence.
Keywords: Antibiotic resistance; Antibiotic resistant bacteria; Enterobacteriaceae; Escherichia coli; Staphylococcus aureus; Systematic review; Transmission; Infectious Diseases